The Influence of Exercise Motivation on Exercise Adherence Intention Among Fitness Center Users: Focusing on the Mediating Role of Self-Efficacy - Long-Zhe Li; Sang-Eun Seo; Kyong-Keun Choi (The Asian Journal of Kinesiology)
OBJECTIVES This study aimed to examine the structural relationships between exercise motivation (internal and external), self-efficacy, and exercise adherence intention among fitness center users. Grounded in social cognitive theory, this study specifically examined whether self-efficacy mediates the effects of internal and external motivation on exercise adherence intention. METHODS A cross-sectional survey was conducted with 298 fitness center participants using a structured questionnaire. The questionnaire measured internal and external motivation, self-efficacy, and intention to adhere to exercise using validated scales on a 5-point Likert scale. Reliability and validity were tested using Cronbach’s α, factor analysis, and correlation analysis. Hypotheses were verified using multiple regression and mediation analysis to evaluate both direct and indirect effects. RESULTS External motivation initially had a significant direct effect on exercise adherence intention in the initial model (β = 0.129, p < 0.05), which became insignificant after including self-efficacy, indicating a full mediation effect. In contrast, internal motivation maintained a strong direct effect (β = 0.338, p < 0.001) as well as an indirect effect through self-efficacy. Self-efficacy significantly mediated both the external and internal motivation pathways, serving as a critical psychological variable in sustaining exercise behavior. CONCLUSIONS The findings underscore the stronger influence of internal motivation over external motivation in promoting sustained exercise behavior. Self-efficacy serves as a pivotal mediator, particularly in transforming externally driven motives into sustained exercise adherence. Practitioners should focus on designing exercise programs that enhance self-efficacy and strengthen internal motivational drivers to promote continued participation. This study provides theoretical and practical implications for fitness center programming and individualized motivation-based interventions.